Positive mental health in Slovenia before and during the COVID-19 pandemic - Matej Vinko; Petra Mikolič; Saška Roškar; Helena Jeriček Klanšček (Frontiers Media S.A., 2022)
BackgroundMental health has been heavily affected during the COVID-19 pandemic. In this study we compared the prevalence of flourishing and languishing mental health during the pandemic and examined which factors are associated with either category of positive mental health respectively.MethodsData from two cross-sectional surveys with nationally representative samples of adult population in Slovenia conducted in 2019 (n = 9,047) and in 2021 (n = 3,429) are used. Positive mental health was measured with Mental Health Continuum-Short Form instrument. Logistic regression was used to examine the associations between flourishing and languishing mental health and relevant COVID-19 specific and other health-related factors.ResultsThere was a substantial decrease in the prevalence of flourishing and an increase in the prevalence of languishing mental health during the pandemic. Distribution of both flourishing and languishing mental health followed the socio-economic gradient. Resilience, COVID-19 literacy and changes in family relations, social interactions, and dietary habits were associated with both flourishing and languishing mental health.ConclusionPositive mental health of the population worsened during the pandemic, more so in traditionally disadvantaged populations. Public health efforts need to be focused appropriately with an increased emphasis on strengthening resilience and health literacy.